EFL TEACHERS’ PREFERENCES AND CHALLENGES IN ONLINE TEACHER PROFESSIONAL DEVELOPMENT - Ramli, Astri Mardilla; Suryati, Nunung; Wulyani, Anik Nunuk; Cahyono, Bambang Yudi (Language Circle: Journal of Language and Literature, 2025)
Nowadays, English as a foreign language (EFL) teachers have a wide range of options to participate in Online Teacher Professional Development (OTPD) due to the availability of various online learning platforms. This study reports the results of exploring EFL teachers' preferences and challenges in using online learning platforms to elevate their teaching practices. Mixed-methods design with a survey for the quantitative element and semi-structured interviews for the qualitative element were used to obtain the data. The participants of the study were thirty Indonesian EFL teachers with active participation in using online learning platforms. The findings demonstrated that in OTPD, EFL teachers preferred to have synchronous interaction, digital reading materials, individual learning strategies, short course duration, a certificate-granting course, and a cost-free course.  The findings also revealed the challenges that EFL teachers encountered in OTPD were unreliable internet connections, limited internet quota, lack of information about available OTPD, inadequate infrastructure during OTPD, lack of support from employer, and difficulties in sustaning motivation as well as commitment during OTPD. These results could be used as considerations in planning and implementing OTPD programs in the future. New OTPD programs should be specifically tailored to the preferences and challenges that EFL teachers have identified.